EFEKTIVITAS BELAJAR SISWA SMAN 1 BEKASI MELALUI MEDIA PEMBELAJARAN DIGITAL - Faiz, Ahmad; Akhdan, Fakhri; Raihan, Muhammad; Alam, Dede Rubai Misbahul (Jurnal Kinerja, 2025)
Living in the 21st century necessitates the integration of digital technology into nearly all aspects of life, including education. However, in practice, many students, including those at SMAN 1 Bekasi, tend to utilize digital technology particularly smartphones more for entertainment and social media than for educational purposes. Data indicate that approximately 88% of SMAN 1 Bekasi students are proficient in using smartphones, yet their academic performance remains low. This situation reflects a decline in learning effectiveness that must be addressed. This study aims to enhance student learning effectiveness through the use of digital-based instructional media, specifically instructional videos uploaded to YouTube by teachers acting as “YouTuber Teachers.” The method employed is a best practice study using a qualitative descriptive approach. Learning media were developed using laptops and smartphones, supported by applications such as PowerPoint, Format Factory, and Viva Video. The instructional videos were uploaded to the YouTube channel Estin Farida and distributed via social media, accompanied by books or interactive modules. The results show that implementing YouTube-based instructional videos significantly improves student learning effectiveness. This is reflected in enhanced learning quality, increased learning motivation and engagement, better preparedness to receive lessons, and greater flexibility in time and space for learning. Additionally, there is a notable improvement in students’ creativity and digital literacy.